Development of Student Worksheets Based on Children Learning in Science Model to Improve HOTS Ability On Circulatory System Material - Darwis, Syaiful Alim; Zulfiani*, Zulfiani; Fadilah, Eva; Camara, Jun S (Universitas Syiah Kuala, 2024)
Increasingly complex problems in the 21st century require skills to be able to solve and find solutions.This research aims to produce student worksheets (SWs) based on the children learning in science (CLIS) model to improve higher order thinking skills (HOTS) on the circulatory system material, as well as seeing the responses of teachers and students to the SWs. The research method used is development research of the ADDIE model (analyze, design, development, implementation, evaluation) using all five stages. The validity of the SWs, teacher and student responses, and improvement of HOTS ability, respectively, are known through expert validation tests, readability tests, response tests, and n-gain tests. The final product developed received a total average percentage of 85.48% with very good criteria in the expert validation test; and 88.23% with very good criteria in the readability test. The teacher's response to the SWs was in very good criteria with a total percentage of 82.56%. The students' response to the SWs was in very good criteria with a total percentage of 83.10%. There was an increase in students' HOTS ability after using SWs by 0.33 with moderate criteria. Based on the research results, it can be concluded that the SWs research results are suitable for use in Integrated Science learning to improve students' HOTS ability